Simultaneous isolation of superior and inferior pulmonary veins on both the left and right sides could yield better outcomes in patients with paroxysmal atrial fibrillation. Issue 5 (24th January 2015) - Takigawa, Masateru; Kuwahara, Taishi; Takahashi, Atsushi; Okubo, Kenji; Takahashi, Yoshihide; Nakashima, Emiko; Yamao, Kazuya; Watari, Yuji; Nakajima, Jun; Takagi, Katsumasa; Fujino, Tadashi; Kimura, Shigeki; et al.
Abstract : Aims: This study investigated whether disappearance patterns of pulmonary vein (PV) potentials (PVPs) during PV isolation (PVI) affect the outcome of catheter ablation (CA) in patients with paroxysmal atrial fibrillation (PAF). Methods and Results: Extensive PVI was performed in 1149 PAF patients (age, 61 ± 10 years). Clinical and demographic characteristics, ablation data, and follow-up outcomes were prospectively collected. During an initial CA, simultaneous disappearance of superior and inferior PVPs in both right and left PVs was observed in 464 (40.4%) patients (Group S). Atrial fibrillation-recurrence free rates at 1, 3, and 5 years after the initial CA in Group S were 78.9, 71.9, and 68.1%, respectively, which were higher than those in Group Non-S ( P = 0.004). However, those were similar after the final CA between both groups. The incidence of PV–left atrium (LA) electrical reconnection was significantly lower in Group S than in Group Non-S in the second (Group S, 65.6% vs. Group Non-S, 82.1%; P = 0.004) and third (Group S, 8.3% vs. Group Non-S, 47.6%; P = 0.03) CAs. Furthermore, the reconnections more frequently occurred on the side of PVs where simultaneous PVP elimination had not been achieved at the initial CA. Simultaneous disappearance of superior and inferior PVPs in both right and left PVs independently reduced the risk of AF recurrence after the initial CA by 26%. Conclusions: The simultaneous disappearance of superior and inferior PVPs in both right and left PVs is associated with less frequent PV–left atrium reconnection and may yield a better clinical outcome after the initial CA.